Existence of Solutions for Sturm-Liouville Boundary Value Problem of Impulsive Differential Equations. (6th June 2012) - Sun, Hong-Rui; Li, Ya-Ning; Nieto, Juan J.; Tang, Qing
Abstract : This paper is concerned with the existence of solutions for Sturm-Liouville boundary value problem of a class of second-order impulsive differential equations, under different assumptions on the nonlinearity and impulsive functions, existence criteria of single and multiple solutions are established. The main tools are variational method and critical point theorems. Some examples are also given to illustrate the main results.